Chromatographic methods enabling the characterization of stationary phases and retention prediction in high‐performance liquid chromatography and supercritical fluid chromatography. Issue 1 (25th November 2015) - Sykora, David; Vozka, Jiri; Tesarova, Eva
Abstract : In the scope of the present review, the current status of high‐performance liquid chromatography/ultra‐high performance liquid chromatography and supercritical fluid chromatography is briefly provided. These techniques and their retention mechanisms are compared. Various alternative approaches utilized for the determination and description of the retention processes in these two systems are mapped. Two frequently used concepts, linear‐free energy relationships, and hydrophobic subtraction models, used for the characterization of the retention interactions, are discussed. Principles and selected applications of the both methods are also covered. Then the models applied for the prediction of retention behavior of solutes on stationary phases are outlined. The procedures utilized for the sorbent/column classification are also covered. Simple chromatographic tests frequently used for the basic characterization and mutual comparison of stationary phases are summarized and briefly commented on. The importance of a statistical evaluation of complex retention data obtained from the chromatographic measurements is outlined. Finally, computer simulations aiming at the facilitation of the quest to optimize separation conditions for a given mixture of analytes are touched upon.